Refleksi Perlawanan terhadap Bullying: Antara Kepedulian dan Ketidaksadaran - Naufal Hibatul Wafi; Windi Putri Oktapiani; Intan Nuraeni; Zahra Davika Mulyani (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores resistance to bullying through a reflective-narrative approach that examines the tension between care and social unawareness within a school context. Drawing on the experience of an anti-bullying seminar conducted at a junior high school, the research analyzes students’ narratives, observations, and anonymous reflections as social texts that reveal moral positions and everyday practices. The findings indicate that care emerges as a subtle form of moral resistance, expressed through empathy, listening, and symbolic support for victims, while unawareness is sustained through normalization, cultural expectations, power relations, and digital interactions. Reflective processes enable students to reinterpret joking, silence, and conformity as practices that may contribute to harm, generating cognitive and ethical shifts. Rather than viewing resistance as a single act, the study highlights it as a gradual process rooted in reflection and relational awareness. By connecting personal experiences with ethical principles and human dignity, this research contributes to broader discussions on bullying as a structural and moral issue. The study underscores the importance of reflective spaces in education to foster critical awareness and sustainable anti-bullying cultures.